13p+19=-98
13p=-98-19
13p=-117
p=-9
2006-12-29 05:26:32
·
answer #1
·
answered by andreea 2
·
2⤊
0⤋
13p + 19= -98
13p + 19 - 19 = -98 - 19 [subtract 19 from both sides]
13p = -117
13p/13 = -117/13 [divide both sides by 13]
p = -9
Double check the answer by plugging in p = -9 to the initial equation.
2006-12-29 13:36:43
·
answer #2
·
answered by Wendy C 2
·
1⤊
0⤋
If 13 p + 19 = -98
Then, 13p = -98-19
13p = -117
-117/13 = p
======> p = - 9
2006-12-29 13:22:26
·
answer #3
·
answered by Plínio 4
·
2⤊
0⤋
13p + 19 = 98
13p + 19 - 19 = - 98 - 19
13p = - 117
13p / 13 = - 117 / 13
p = - 9
The answer is p = - 9
Insert the p value into the equation
- - - - - - - - - - - - -- - - - - - -- - -
13p + 19 = - 98
13( - 9) + 19 = - 98
- 117 + 19 = - 98
- 98 = - 98
- - - - - - - -s-
2006-12-29 13:49:33
·
answer #4
·
answered by SAMUEL D 7
·
0⤊
0⤋
First: subtract 19 from both sides > opposite side means opposite sign:
13p + 19 - 19 = - 98 - 19
13p = -117
Second: solve for "p" and keep it on one side > divide both sides by 13:
13p/13 = -117/13
p = -9
2006-12-29 13:40:12
·
answer #5
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
13p+19= -98
13p= -98-19
13p= -117
=> p = -9
2006-12-29 13:30:29
·
answer #6
·
answered by _PeTaL_D`oR_ 2
·
1⤊
0⤋
Subtract 19 from both sides:
13p=-117
Divide 13 from both sides:
p=-9
Check:
13(-9)+19=-98
-117+19=-98
-98=-98
2006-12-29 13:28:17
·
answer #7
·
answered by Anonymous
·
1⤊
0⤋
13p + 19 = -98
13 p = -98 - 19 = - 117
p = -117 / 13 = 9
2006-12-29 13:14:41
·
answer #8
·
answered by saudipta c 5
·
0⤊
1⤋
13p+19= -98
-13p= -117
p= 9
2006-12-29 13:17:50
·
answer #9
·
answered by 7
·
0⤊
1⤋
13p+19=-98
-19 -19
13p=-117
13p/13=p
-117/13=-9
p=-9.
2006-12-29 13:13:15
·
answer #10
·
answered by Greg M 2
·
2⤊
0⤋